(3GdHGgQ aj GdfGQfLjGJs - (3GHf TgjO GdGTLYj , CMeO Hf YHO Gdedc Hf CMeO Hf TgjO, CHh YGeQ GdGTLYj,J (B426 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfG QCjfG CcKQ GdMjd hGdfhGejS hGdeNGQja hGdJdHjS s
(3BNQgG (B:s
(3ef dbjg SHY adjcTa Yf PcQg hdjhGLgg Hg, aEfg dGjba SGYg hGMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B302s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B151 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HGSJGfHhd (B(2918) s
Keywords: (3GdMQha h GdChaGbs